Red Balloon Rock Shelter: Iron Age and Middle Stone Age occupations on the Waterberg Plateau in Limpopo, South Africa - Wadley, Lyn; Mauran, Guilhem; Sievers, Christine; van Deventer, Hennie; Biemond, Wim; Seanego, Klaas; Li, Bo; Jacobs, Zenobia (Southern African Humanities, 2021)
Red Balloon Rock Shelter is located at 1200 m above mean sea level on the Waterberg Plateau, Limpopo Province. The surface of the deep, dry shelter is strewn with Iron Age ceramics of many facies, and Middle Stone Age (MSA) lithics. It may have been used as a rain-making site from the time of the first Iron Age settlement in the area. In addition to ceramics, there are many ostrich eggshell beads, some worked bone, and seeds that imply vegetation similar to the current vegetation, and the possible use of red balloon (Erythrophysa transvaalensis) seeds as beads. There was, however, probably no agropastoralist occupation within the shelter until the difaqane or just before it. A single preliminary date of 250±80 BP on charcoal from a large hearth supports an interpretation of the shelter as a Tswana rain-control site. The long hiatus between this refugium and the MSA occupation is not geologically marked. The shelter was first inhabited by people close to 100 000 years ago when stone tool-makers were using Levallois, blade, and bipolar flaking for a variety of lithic products that included scrapers, denticulates, points, and backed tools. The lithics were coated in dried mud, suggesting that a wetter than present phase followed the last of the MSA occupations in the shelter.